2018
DOI: 10.1007/s11136-018-1805-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of midlife value priorities with health-related quality of life, frailty and mortality among older men: a 26-year follow-up of the Helsinki Businessmen Study (HBS)

Abstract: Value priorities of men assessed in midlife had long-term associations with HRQoL and frailty in old age, and they may also predict mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…In the HBS cohort, we have observed the relationship between cardiovascular risk factors in midlife and health-related quality of life (HRQoL) in old age [ 16 19 ]. In addition, studies have shown an association between midlife value priorities [ 20 ], behavioral factors [ 15 ], and self-rated health (SRH) [ 21 ] with late-life frailty and mortality. In a cross-sectional study of the HBS cohort, < 5% met the criteria for AHA, which was associated with physical functioning and subjective health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the HBS cohort, we have observed the relationship between cardiovascular risk factors in midlife and health-related quality of life (HRQoL) in old age [ 16 19 ]. In addition, studies have shown an association between midlife value priorities [ 20 ], behavioral factors [ 15 ], and self-rated health (SRH) [ 21 ] with late-life frailty and mortality. In a cross-sectional study of the HBS cohort, < 5% met the criteria for AHA, which was associated with physical functioning and subjective health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%